MASS CULTURE AND CONSCIOUSNESS IN THE PROCESS OF GLOBALIZATION - Дротянко, Л. Г. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article is dedicated to the philosophical analysis of a mutual influence of mass culture and consciousness in the globalized world. The main tendencies of this influence with the general use of ICT are revealed.